The use of Think, Talk, and Write (TTW) model to foreign students learning Indonesian language at Overnewton College - Anggi Trinanda Harahap; Nursaid Nursaid (Jurnal Bahasa Indonesia bagi Penutur Asing, 2022)
This research was conducted with the aim of knowing how students at Overnewton College learned Indonesian using the Think, Talk, and Write (TTW) learning model. This research was conducted online using Zoom as media. This research uses qualitative research with the descriptive-analytical method. The study used 11th grade students as the sample in this study. This study also examines how students' perspectives on learning are carried out and analyzes students' writing skills. Research finds that using the Think, Talk, and Write (TTW) model in learning the Indonesian language for foreign students can help students practice their speaking and writing skills in Indonesian. In conducting learning using the think, talk, write model, there are three primary stages students must go through to understand, that is, (1) think, (2) speaking, and (3) writing or expressing thoughts through written media.  In general, students' perceptions on the learning are good. Besides, students also feel happy with the learning because it uses audio-visual media that can help students' listening skills